2015
DOI: 10.1111/febs.13188
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from gain‐ and loss‐of‐function models of pro‐survival Bcl2 family proteins: implications for targeted therapy

Abstract: Cell survival depends on the maintenance of mitochondrial integrity controlled by a well-balanced interplay between anti-and pro-apoptotic B cell lymphoma 2 (Bcl2) family members. Given their frequent deregulation in human pathologies, including autoimmunity and cancer, significant research efforts have increased our molecular understanding of how Bcl2 proteins control cell death. This has fostered the development of small non-peptidic compounds, so-called BH3-mimetics, that show excellent prospects of passing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 122 publications
(199 reference statements)
3
47
0
1
Order By: Relevance
“…Additional cell cycle regulator CDKN1B was significantly downregulated in PDTCs (Table 2). Finally, we demonstrate that the apoptosis related gene BCL2, previously reported to be associated with a number of malignancies by other groups [16, 17], exhibits a downregulation in FTC, PTC and PDTC, with a progressive increase in fold change associated with malignancy progression (Table 5, [8]).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Additional cell cycle regulator CDKN1B was significantly downregulated in PDTCs (Table 2). Finally, we demonstrate that the apoptosis related gene BCL2, previously reported to be associated with a number of malignancies by other groups [16, 17], exhibits a downregulation in FTC, PTC and PDTC, with a progressive increase in fold change associated with malignancy progression (Table 5, [8]).…”
Section: Discussionsupporting
confidence: 62%
“…Alterations in CHEK1 levels have been previously described by us in PTC (Table 5, [8]), and in a number of non-thyroid malignancies by other groups [16, 17]. A recent report reveals that CHEK2 (but not CHEK1 ) levels are altered in PDTC and ATC [18].…”
Section: Discussionmentioning
confidence: 60%
“…On the other hand, several observations also argue against this model. First, it has been observed that Mcl1 gene deletion is lethal in a variety of cell lineages [104109], although this might reflect an obligate role for Mcl-1 in oxidative phosphorylation within mitochondria rather than its anti-apoptotic role on the surface mitochondria [106]. Moreover, recent results suggest that the relative potencies of these proteins might reflect their relative expression levels rather than the range of pro-apoptotic proteins neutralized [110].…”
Section: Advances In Understanding Regulation Of Anti-apoptotic Bcmentioning
confidence: 99%
“…Deletion of individual anti-apoptotic Bcl-2-proteins in mice produces rather different phenotypes, ranging from male sterility (deletion of Bcl-w) and cell death of specific populations in various organs (loss of Bcl-2) to embryonic lethality (loss of Bcl-X or Mcl-1). 9 …”
mentioning
confidence: 99%